Instant Cassandra Query Language : a Practical, Step-by-Step Guide for Quickly Getting Started wtih Cassandra Query Language /: a Practical, Step-by-Step Guide for Quickly Getting Started wtih Cassandra Query Language. (2013) - Singh, Amresh
No abstract available